Bleach Effectively in Removes The Stubborn Stains - Moondra Zubir; Ayi Darmana; Marini Damanik; Hafni Indriati Nasution; Osi Annauli G; Vrili Coirala Rama Uli Siregar; Yosi Santika Silitonga (Universitas Negeri Medan, 2020)
Along with the development of science and technology, more and more types of manufactured goods produced to meet our needs we need to know that among these materials there are dangerous or toxic, therefore it is very important for us to know the type, nature, usefulness, as well as the dangers of every chemical that we use at home As we know, all kinds of objects that are around us are actual material, all material consists of chemicals but, in our daily lives we commonly use the term material instead of chemicals. Clothing that we use every day will be prone to stains so it is important to know how to remove stubborn stains on clothes. It would be very inconvenient if the clothes worn are dirty and not beautiful to the eye. There are many types of stains, ranging from dirty sweat, blood, residual makeup, black spots caused by fungus, to stains from the outside such as stains caused by rust, paint, oil, ink or spills of food and drinks. If you use the wrong method to remove these stains, it is not uncommon for us to find difficulties and can even be fatal as they get dirty. Each type of stain has a different treatment, depending on the nature of the stain. Bleach is now available as a solution to the problem of stains on these clothes.